2012
DOI: 10.1111/j.1756-8765.2011.01178.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Human Navigation Using Network Analysis

Abstract: We have considered a simple word game called the word-morph. After making our participants play a stipulated number of word-morph games, we have analyzed the experimental data. We have given a detailed analysis of the learning involved in solving this word game. We propose that people are inclined to learn landmarks when they are asked to navigate from a source to a destination. We note that these landmarks are nodes that have high closeness-centrality ranking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
3
25
1
Order By: Relevance
“…The present finding adds to an increasing amount of evidence that suggests that the structure of the lexical network—as described in Vitevitch (2008) and Arbesman et al (2010)— influences the speed and accuracy of various aspects of lexical processing (e.g., Chan & Vitevitch, 2009, 2010; Iyengar et al, 2012; Vitevitch et al, 2011; Vitevitch, Chan & Goldstein, 2013). It has been recognized for some time that the structure of the lexicon influences lexical processing.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The present finding adds to an increasing amount of evidence that suggests that the structure of the lexical network—as described in Vitevitch (2008) and Arbesman et al (2010)— influences the speed and accuracy of various aspects of lexical processing (e.g., Chan & Vitevitch, 2009, 2010; Iyengar et al, 2012; Vitevitch et al, 2011; Vitevitch, Chan & Goldstein, 2013). It has been recognized for some time that the structure of the lexicon influences lexical processing.…”
Section: Discussionsupporting
confidence: 61%
“…The time it took to find a solution dropped from 10–18 minutes in the first 10 games, to about 2 minutes after playing 15 games, to about 30 seconds after playing 28 games, because participants would “morph” the start-word (e.g., bay ) into one of the landmark words that were high in closeness centrality (e.g., aid ), then morph the landmark-word into the desired end-word (e.g., egg ). Although this task is a contrived word-game rather than a task that assesses on-line lexical processing, the results of Iyengar et al (2012) nevertheless support the idea that (orthographic) word-forms may indeed be organized like a network in the mental lexicon, and that the tools of network science can be used to provide insights about cognitive processes and representations.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…It has also been suggested that generating and deciphering language can be usefully modelled as navigation on language networks by means of various strategies [47] such as random walks [48], switching random walks [49], random walks with memory [50], and using ‘landmarks’ with high network closeness centralities [51]. We further propose that linguistic networks contain shortcuts that optimizes their ease of navigation and access.…”
Section: Syntactic Network Of Languagesmentioning
confidence: 99%